Directed Self-Assembly of Heterologously Expressed Hagfish EsTKα and EsTKγ for Functional Hydrogel - Sun, Ruishuang; Zheng, Ruonan; Zhu, Wenlong; Zhou, Xiqin; Liu, Luo; Cao, Hui (Frontiers in Bioengineering and Biotechnology, 2022)
The proteins found in hagfish slime have long been considered useful because of their potential to be fabricated into novel green, environmental, functional bionic material. The two main component proteins in the slime thread of hagfish, (opt)EsTKα and (opt)EsTKγ, were used as raw materials. However, the methods available to assemble these two proteins are time- and labor-intensive. The conditions affecting protein self-assembly, such as the pH of the assembly buffer, protein concentration, and the protein addition ratio, were the subject of the research. Through a series of tests, the self-assembly results in a variety of assembly conditions were explored. Finally, a simplified protein self-assembly method was found that allows simple assembly of the two proteins directly. This method does not require protein purification. Its assembly conditions are: the assembled dialysate pH is 9, the temperature is 4℃, the (opt)EsTKα and γ protein concentrations are both 1.0 mg/mL, and the addition ratio is 1:1. Under these conditions, a new gel material was synthesized from the hagfish protein through self-assembly of the two proteins. This assembly method has the benefits of being a simple, time-saving, and efficient. The self-assembled protein gel products were verified by SDS polyacrylamide gel electrophoresis and contained (opt)EsTKα and γ proteins. The self-assembled protein gel was freeze-dried and observed under a scanning electron microscope (SEM). The self-assembled protein formed a dense, three-dimensional porous network structure, meaning that it had good water retention. Observing the gel with atomic force microscopy (AFM) showed that the surface of the protein fiber skeleton has the network-like structure of gel and is relatively smooth. Characterization by circular dichroism (CD) and Fourier transform infrared spectroscopy (FT-IR) demonstrated that the two proteins were successfully assembled, and that the assembled protein had a secondary structure dominated by α-helices. The rheological properties of the self-assembled products were tested to confirm that they were indeed hydrogel property.